Pelanggaran Etika Pariwara dalam Iklan Judi Online di Situs Web Pusat Film21 - Naufal Azzuhdi, Abdurrohman; Listya Kumara, Anindya; Fatihi; Junaedi, Fajar (Universitas Muhammdiyah Yogyakarta, 2025)
This study aims to identify ethical violations in Online gambling advertisements displayed on the Pusat Film website, focusing on the marketing strategies used in these advertisements. Based on an analysis of Online gambling ads found on the site, the research reveals that many of these ads violate the Indonesian Advertising Ethics (EPI) and relevant legal regulations, particularly Article 27, Clause 2 of the Information and Electronics Transaction Law, which prohibits Online gambling promotions. These advertisements employ unethical marketing strategies, such as unrealistic claims of significant profits and seductive visuals that exploit sexual appeal. The impact of these ads can increase individual involvement in illegal gambling, worsen the normalization of gambling in society, and exacerbate Online gambling addiction. The study employs a qualitative method using documentation and literature review techniques to analyze the content of the ads and assess the ethical violations present. The findings highlight the need for stricter oversight of Online gambling advertisements on digital platforms to protect consumers from negative consequences, such as addiction and financial loss.